Asymmetric Synthesis of (-)-6-Desmethyl-Fluvirucinine A(1) via Conformationally-Controlled Diastereoselective Lactam-Ring Expansions - Moon, Hyunyoung; Yoon, Hojong; Lim, Changjin; Jang, Jaebong; Yi, Jong-Jae; Lee, Jae Kyun; Lee, Jeeyeon; Na, Younghwa; Son, Woo Sung; Kim, Seok-Ho; Suh, Young-Ger (MDPI, 2018)
The versatile synthesis of (-)-6-desmethyl-fluvirucinine A(1) was accomplished at a 24% overall yield through a thirteen-step process from a known vinylpiperidine. The key part involved the elaboration of the distal stereocenters and a macrolactam skeleton via conformationally-induced diastereocontrol and the iterative aza-Claisen rearrangements of lactam precursors.
Keywords: INFLUENZA-A VIRUS; ENANTIOSELECTIVE TOTAL-SYNTHESIS; AZA-CLAISEN REARRANGEMENT; N,O-ACETAL TMS ETHER; ANTHELMINTIC MACROLACTAMS; VERSATILE CONVERSION; SCH 38516; FLUVIRUCIN-B2; ALKALOIDS; AGLYCON